2021
DOI: 10.3390/ijms22031277
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Ellagic Acid on Keratinocytes via MAPK and STAT Pathways

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease that is characterized by an impaired skin barrier and intense itchiness, which decreases the individual’s quality of life. No fully effective therapeutic agents have prevailed for AD due to an insufficient grasp of the complex etiology. Ellagic acid (EA), a natural compound, has anti-inflammatory properties in chronic diseases. The effects of EA on AD have not yet been explored. The present study investigated the effects of EA on TNF-α/IFN-γ-stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 48 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…In recent decades, EA is attracting great attention due to its pronounced antioxidant [15][16][17][18][19][20][21][22][23], anti-inflammatory [24][25][26][27][28][29], antimutagenic [30][31][32][33], and antiproliferative properties [34][35][36][37][38][39] and its therapeutic potential in the treatment of several human diseases. Numerous studies have shown that EA may be involved in regulating a spectrum of cellular signaling pathways to prevent, mitigate, or slow down the progression of chronic disorders, including cardiovascular [40][41][42][43] and neurodegenerative diseases [44][45][46][47], diabetes [48][49][50][51], and cancer [38,[52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, EA is attracting great attention due to its pronounced antioxidant [15][16][17][18][19][20][21][22][23], anti-inflammatory [24][25][26][27][28][29], antimutagenic [30][31][32][33], and antiproliferative properties [34][35][36][37][38][39] and its therapeutic potential in the treatment of several human diseases. Numerous studies have shown that EA may be involved in regulating a spectrum of cellular signaling pathways to prevent, mitigate, or slow down the progression of chronic disorders, including cardiovascular [40][41][42][43] and neurodegenerative diseases [44][45][46][47], diabetes [48][49][50][51], and cancer [38,[52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…The compound can moreover modulate the mitogen-activated protein kinase/extracellular signal-regulated protein kinase (MEK1/2-ERK) and the Janus kinase signal transducer/activator of transcription (JAK/STAT) pathways in response to the treatment of the cells with pro-inflammatory factors TNF-α and interferon γ (IFN-γ). 73 Cellular targets of luteolin involve the major pathways regulating inflammation - Nf-κB, activator protein 1 (AP-1) and signal transducer and activator of transcription (STAT-3). 74 N-acetyl glucosamine (NAG) normalizes the stratum corneum by up-regulation of the differentiation markers keratin 10 and involucrin.…”
Section: Current Treatments For Skin Hyperpigmentation: Unique Requir...mentioning
confidence: 99%
“…Several studies have demonstrated anti-inflammatory properties of ellagic acid, a dimeric derivative of gallic acid abundant in blackberry seeds, and present in many different plant species [ 3 , 85 , 86 , 87 ].…”
Section: Chemical Content Of Seeds Eaten With Whole Fruit and Biologi...mentioning
confidence: 99%
“…In HaCaT (human, adult, low calcium, and high temperature) keratinocytes stimulated by tumor necrosis factor α (TNF-α) and interferon γ (IFN-γ), 250–1000 μM ellagic acid suppressed the expression of pro-inflammatory interleukin 6, and decreased relative mRNA expression of chemokines—thymic stromal lymphopoietin (TSLP), macrophage-derived chemokine (MDC), and thymus and activation-regulated chemokine (TARC). Furthermore, it inhibited pro-inflammatory Janus kinase/signal transducer and activator of transcription (JAK/STAT) and phosphoinositide 3-kinase/AKTsignaling pathways [ 86 ].…”
Section: Chemical Content Of Seeds Eaten With Whole Fruit and Biologi...mentioning
confidence: 99%